Pengaplikasian Pembelajaran Seni Gerak Dan Tari Anak Usia Dini di RA Tanjung Morawa - Hilda Zahra Lubis; Siti Nur Jannah; Cindi Octavia; Nur Hidayatun; Khalida Ziah Sukma Siregar (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Learning the art of movement and dance cannot be separated from the name music, they are interconnected to complement each other. Learning the art of movement and dance at RA Tanjung Morawa introduces simple dance movements that are easy for young children to imitate. The aim of this article is to be able to apply it to children. This qualitative article uses data collection techniques, observations, interviews and documentation. The results of learning movement arts and dance for children using the method: 1) Introduction to movement in dance. 2) Achievements of indicators that children can achieve well-developed aspects of art and physical motor skills. 3) Play using children's musical instruments while doing simple dance movements.